2009
DOI: 10.1111/j.1744-7348.2008.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal genetic diversity and populational genetic differentiation in Phragmites australis distributed in the Songnen Prairie in northeast China as revealed by amplified fragment length polymorphism and sequence‐specific amplification polymorphism molecular markers

Abstract: Genetic variation within and between four naturally occurring Phragmites australis land populations, DBS, QG, SS1 and SS2 (named after locality), which colonise distinct habitats (different edaphic conditions) in the Songnen Prairie in northeast China, were investigated by amplified fragment length polymorphism (AFLP) and sequence‐specific amplification polymorphism (S‐SAP) markers. It was found that the selected primer combinations of both markers were highly efficient in revealing the inter‐clonal genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…As such, this species is distributed widely across the Songnen Prairie in northeastern China. P. australis often grows as a companion species in alkalized meadows but forms monodominant communities in local low-lying areas or saline-rich/alkaline patches (Li et al, 2009). This species is used as a major forage grass in the Songnen Prairie due to its high level of productivity and high protein content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, this species is distributed widely across the Songnen Prairie in northeastern China. P. australis often grows as a companion species in alkalized meadows but forms monodominant communities in local low-lying areas or saline-rich/alkaline patches (Li et al, 2009). This species is used as a major forage grass in the Songnen Prairie due to its high level of productivity and high protein content.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the between-habitat genetic differentiation of P. australis on a small spatial scale (Pellegrin and Hauber, 1999;Guo et al, 2003;Gao et al, 2012). A preliminary investigation of the genetic diversity of this reed in the Songnen Prairie showed extensive genetic variability across a certain geographic range (Li et al, 2009). However, the within-and between-habitat genetic diversity and differentiation on a small spatial scale in the Songnen Prairie have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the same thought, it seems that human assisted hybrids breeding and also microbial genomic attacks in plants could at times lead to deleterious epigenetic interactions in plants that can cause hindrances in gene flow in plants. This can also trigger other epigenetically induced regulatory genes and elements like retrotransposons in diverse populations as was observed in Phragmites australis populations (Li et al, 2009). Such interactive implications can provide an explanation in the search for full understanding of the molecular basis of hybrid necrosis.…”
Section: Resultsmentioning
confidence: 84%
“…Such habitat fragmentation and other physical barriers like mountains, human activities, shielding vegetations and accumulation of valleys could influence the flow of wind and movement of dispersal agents. Further more, recent studies by Li et al, 2009, showed a remarkable observation in their cluster analysis indicating that the soil condition and the proximal distance between the populations have a significant influence in the genetic www.intechopen.com diversity analysis. Hence, it is now conceivable that the occurrence and spectra of genetic variations both within a plant population and among populations can be caused by three distinct as well as interlaced factors.…”
Section: Inter-clonal Genetic Diversitymentioning
confidence: 99%
“…These could interfere with wind and pollinator movements (Li et al, 2009) causing homogenization of clones. This possibility was evidenced by an exceptionally low level of gene flow between two populations of L. chinensis (Zhang et al, 2009).…”
Section: Habitat Inducement and Epigenetic Influences In Genetic Divementioning
confidence: 99%